ANALYSIS OF ECOTOURISM DEVELOPMENT OF SEMBILANGAN BEACH: CHARACTERS, FACTORS, AND CHALLENGES - Rita Parmawati; Agung S. Kurnianto; Afrilyani Kontrayana; Azzah F. Cholis; Herman Hidayat; Wilda Al Aluf (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2018)
Sembilangan beach in Bangkalan, East Java Province, Indonesia, is one of the potential and growing areas for ecotourism. This beach has several aspects of ecotourism development that has not been professionally managed to achieve ecotourism goals. The purpose of this study is to analyze the factors supporting the process of ecotourism development in Sembilangan beach, both in terms of visitors and the community. This knowledge is useful to support the strategic steps to accelerate its development. This research was conducted at Sembilangan beach, Bangkalan, East Java Province. Topics or the independent variables are explored related to the perception of tourists, culture, environmental conditions, community participation, economic conditions, and institutions. Data of the respondents are grouped according to their status: visitors and community. Simultaneous and Partial Test is used to understand the correlation. Environmental, economic and institutional factors have a simultaneous influence on community participation in the development of ecotourism. Environmental conditions partially have the greatest influence on community participation in the development of ecotourism Sembilangan beach